Development of a lung cancer therapeutic based on the tumor suppressor microRNA-34 - Wiggins, Jason F. (2010)
Tumor suppressor microRNAs (miRNAs) provide a new opportunity to treat cancer. This approach, “miRNA replacement therapy”, is based on the concept that the re-introduction of miRNAs depleted in cancer cells reactivates cellular pathways that drive a therapeutic response. Here, we describe the development of a therapeutic formulation using chemically synthesized miR-34a and a lipid-based delivery vehicle that blocks tumor growth in mouse models of non-small cell lung cancer. This formulation is effective when administered locally or systemically. The anti-oncogenic effects are accompanied by an accumulation of miR-34a in the tumor tissue and downregulation of direct miR-34a targets. Intravenous delivery of formulated miR-34a does not induce an elevation of cytokines or liver and kidney enzymes in serum, suggesting that the formulation is well tolerated and does not induce an immune response. The data provide proof of concept for the systemic delivery of a synthetic tumor suppressor mimic, obviating obstacles associated with viral-based miRNA delivery and facilitating a rapid route for miRNA replacement therapy to the clinic.